Tactical silence as a marketing strategy. The case of Elden ring - Petkov, Mikhail (Media and Language, 2023)
An advertising campaign for a product is almost as important as the product itself. In order to gather attention and build excitement, a company must consistently advertise, display and disseminate news about its upcoming project. This rule applies to any type of industry, including the video game industry. However, is it possible for a product to be commercially successful without any effort on the part of the company to make it so? This is the purpose of the present study, which examines the case of the advertising campaign for the video game „Elden Ring“ and the corresponding inaction of its marketing department. The study concludes that the initial excitement caused by the fans may be enough to gain attention, and without much effort on the part of the company. Silence from the developers can also be proven to be a sound tactical decision.
Keywords: video game; advertising campaign; Elden Ring; trailer; computer game